MiR-34a, a promising novel biomarker for benzene toxicity, is involved in cell apoptosis triggered by 1, 4-benzoquinone through targeting Bcl-2. (February 2017) - Chen, Yujiao; Sun, Pengling; Guo, Xiaoli; Gao, Ai
Abstract: Exposure to benzene is inevitable, and concerns regarding the adverse health effects of benzene have been raised. Most investigators found that benzene exposure induced hematotoxicity. In this regard, Our study aimed to explore a novel potential biomarker of adverse health effects following benzene exposure and the toxic mechanisms of benzene metabolites in vitro. This study consisted of 314 benzene-exposed workers and 288 control workers, an air benzene concentration of who were 2.64 ± 1.60 mg/m 3 and 0.05 ± 0.01 mg/m 3, respectively. In this population-based study, miR-34a expression was elevated in benzene-exposed workers. The correlation of miR-34a with the airborne benzene concentration, S-phenylmercapturic acid (S-PMA) and trans, trans-muconic acid (t, t-MA), all of which reflect benzene exposure, was found. Correlation analysis indicated that miR-34a was associated with peripheral blood count, alanine transaminase (ALT) and oxidative stress. Furthermore, multivariate analysis demonstrated that miR-34a expression was strongly associated with white blood cell count (structure loadings = 0.952). In population-based study, miR-34a had the largest contribution to altered peripheral blood counts, which reflect benzene-induced hematotoxicity. The role of miR-34a in benzene toxicity was assessed using lentiviral vector transfection. Results revealed that 1, 4-benzoquinone induced abnormal cell apoptosis and simultaneously upregulated miR-34a accompanied with decreased Bcl-2. Finally, inhibition of miR-34a elevated Bcl-2 and decreased 1, 4-benzoquinone-induced apoptosis. In conclusion, miR-34a was observed to be involved in benzene-induced hematotoxicity by targeting Bcl-2 and could be regarded as a potential novel biomarker for benzene toxicity. Graphical abstract: Highlights: MiR-34a regulated benzene-induced hematotoxicity. MiR-34a mediated 1, 4-benzoquinone-induced apoptosis via targeting Bcl-2. MiR-34a was considered as major factor to abnormal cell apoptosis, involved in benzene-induced hematotoxicity.